Safety evaluation of bakun concrete faced rockfill dam - Ahmad, Hilton@Mohd Hilton (2006)
This study deals with a 2-D plane strain finite element analysis of elastic linear (Hooke's law) and non-linear lastest Duncan-Chang Hyperbolic Model to study the structural response of the dam in respect to the deformation and stresses of Main Dam of Bakun's Concrete face Rockfill Dam (CFRD) project which is currently under construction located in Sarawak, Malaysia as the second highest CFRD in the world when completed. Dead, Birth and Ghost element technique was used to simulate sequences of construction of the dam. The comparison of rigid and flexible foundation on the behaviour of the dam was discussed. In the finite element modeling the concrete slab on the upstream was represented through six-noded element, while the interface characteristic between dam body and concrete slab was modeled using interface element. The maximum settlement and stresses of the cross section was founded and the distribution of them were discussed and tabulated in form of graphs and contours. The effect of reservoir filling loading have gradual effect to the dam response behavior. The computed results by the present method were found to be in good agreement with the comparison of value to the existing dams in the world.